EFEKTIVITAS EKSTRAK DAUN MENGKUDU (Morinda citrifolia L.) DAN DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav) TERHADAP ZONA HAMBAT PERTUMBUHAN Staphylococcus aureus - F.E Afiff; Susie Amilah (FMIPA : Universitas PGRI Adi Buana, 2017)
Has conducted research on the effectiveness of various concentrations of noni leaf extract (Morinda citrifolia L.) And red betel leaf (Piper crocatum Ruiz & Pav) the growth inhibition zone of staphylococcus aureus. Inhibition test using paper disc diffusion method. Paper discs soaked in noni leaf extract and red betel leaf for 30 minutes and placed on media that has been spread bacteria staphylococcus aureus and then incubated for 24 hours. The results showed that noni leaf extract and red betel leaves with a concentration of 40%, 60% and 80% affecting large growth inhibition zone of Staphylococcus aureus.